Eggs, larval morphology development and behavioral changes of jade perch (scortum barcoo) larvae - Jin Naoto; Ching, Fui Fui; Senoo Shigeharu (Zoology Department, Faculty of Science, 2025)
This study examined the embryonic development of Jade perch (Scortum barcoo) during the early larval stage, emphasizing morphology, sensory organ development, and behavioral changes. Artificial reproduction was conducted using one mature female (1.0 ± 0.0 kg) and two mature males (1.0 ± 0.8 kg) through hormone-induced spawning. The fertilization and hatching rates were recorded as 83.4 ± 0.45％ and 86.4 ± 0.78% respectively, and fertilized egg size was 2.73 ± 0.3 mm. Hatching occurred at 20:20 hours after fertilization (hAF) under 27.3 ± 0.7 ℃ and the size of newly hatched larvae was 2.79 ± 0.05 mm, growing up to 4.73 ± 0.07 mm by 90 hours after hatching (hAH). Morphological developments were observed as follows: eye and fin formation at 6 hAH, noticeable pigmentation at 30 hAH, mouth opening at 36 hAH, jaw movement at 42 hAH, and anus opening at 60 hAH. Sensory organs development was observed as follows: lens formation and inner ear formation at 6 hAH, eye pigmentation and olfactory pit formation at 30 hAH. Behavioral changes were observed as follows: onset of vertical swimming at 12 hAH, onset of horizontal swimming at 18 hAH, with larvae showing positive phototaxis and rheotaxis at 30 hAH, and first feeding starting at 72 hAH. This study concludes that Jade perch undergoes normal development, and these primary data can be used to establish a rearing protocol to further enhance the overall growth performance in captivity.